Global Justice and Global Criminal Laws: The Importance of Nyaya in the Quest for Justice after International Crimes - Antony Pemberton; Rianne Letschert (Tilburg Law Review, 2012)
This brief contribution to the debate concerning global law draws on the authors’ analysis of international criminal justice. It argues that the extent to which international criminal law is in fact contributing to global justice in the aftermath of international crimes remains to be seen. In particular, the smooth relationship between international criminal law and the perception of justice can be called into question, as it relies too heavily on the idea that going through the motions of westernized forms of international criminal law will automatically inculcate a sense of justice in victimized populations, while 'en passant' contributing to the resurrection of the rule of law. The connection to broader issues in global justice and global law will draw heavily on Amartya Sen’s recent critique of John Rawls’ Theory of Justice, in which the former employs the ancient Sanskrit notions of 'niti' and 'nyaya'.